Effects of Mindfulness Meditation on Musical Aesthetic Emotion Processing - Liu, Xiaolin; Liu, Yong; Shi, Huijuan; Zheng, Maoping (Frontiers in Psychology, 2021)
Mindfulness meditation is a form of self-regulatory training for the mind and body. The relationship between mindfulness meditation and music aesthetic emotion processing (MAEP) remains unclear. The aim of the current study was to explore the effect of temporary mindfulness meditation on MAEP while listening to Chinese classical folk instrumental musical works. A 2 (groups: mindfulness meditation group, MMG; control group, CG) × 3 (music emotions: calm music, happy music and sad music) mixed experimental design and a convenience sample of university students were used to verify our hypotheses, which were based on the premise that temporary mindfulness meditation may affect MAEP (MMG vs. CG). Sixty-seven non-musically trained participants (65.7% female, age range: 18–22 years) were randomly assigned to two groups (MMG or CG). Participants in MMG were given a single 10-minute recorded mindfulness meditation training before and during music listening. Psychological measurement instruments consisted of the Five Facet Mindfulness Questionnaire (FFMQ) and the Positive and Negative Affect Schedule (PANAS). Self-report results showed no significant between-group differences (PANAS) and so too for the scores of four subscales of the FFMQ (p values greater than 0.05 throughout), except for the non-judging of inner experience subscale. Results showed that temporary mindfulness meditation training decreased the negative emotion experiences of happy and sad music and the positive emotions of calm music during recognition and experience, and promoted beautiful musical experiences in individuals with no musical training. Maintaining a state of mindfulness while listening to music enhanced body awareness and led to experiencing a faster passage of musical time. In addition, it was found that Chinese classical folk instrumental musical works effectively induced aesthetic emotion and produced multidimensional aesthetic experiences among non-musically trained adults. This study provides new insights into the relationship between mindfulness and music emotion.